Skin Aging Profile in Tertiary Hospital: a Descriptive Study - Tasya Wikassa; Damayanti Damayanti; Irfiansyah Irwadi; Trisniartami Setyaningrum; Rahmadewi Rahmadewi; Diah Mira Indramaya; Menul Ayu Umborowati (Faculty of Medicine, Universitas Airlangga, 2022)
Background: Skin aging is a physiological process that involves changes in skin cells and tissues due to abnormal mechanisms and decreased tissue function caused by both intrinsic and extrinsic factors. Skin aging has different clinical manifestations in each individual, which were classified using Glogau's photoaging classification. Purpose: The objective of this descriptive observational study is to evaluate the profile of skin aging patients at Dr. Soetomo General Hospital Surabaya from January – December 2019. Methods: This study utilized a total sampling technique from data obtained from the patients' medical records, which included age, gender, occupation, anamnesis, physical examination, diagnosis, and treatment received by patients. This research has been reviewed by the Ethics Committee at Dr. Soetomo General Hospital Surabaya (0438/KEPK/XII/2021). Result: Based on data obtained from medical records, 415 samples of skin aging patients were collected. The highest number of cases occurred among patients aged 45 - < 60 years. Most patients were female, and the majority of patients’ occupations were private employees. History taking findings include the most common complaint, namely dull skin, with the most precipitating factors discovered in patients, namely exposure to sunlight and pollution. Wrinkles were the most common physical examination finding in patients, with Glogau's photoaging III being the most common diagnosis. Most patients were treated with photoprotection in the form of sunscreen. Conclusion: With the increase of public awareness about appearance, as well as human health and quality of life, skin aging is receiving adequate attention nowadays, with sun exposure being the most common precipitating factor.